New Limits for Stability of Supercapacitor Electrode Material Based on Graphene Derivative - Šedajová, Veronika; Jakubec, Petr; Bakandritsos, Aristides; Ranc, Václav; Otyepka, Michal (Nanomaterials (Basel, Switzerland), 2020)
Supercapacitors offer a promising alternative to batteries, especially due to their excellent power density and fast charging rate capability. However, the cycling stability and material synthesis reproducibility need to be significantly improved to enhance the reliability and durability of supercapacitors in practical applications. Graphene acid (GA) is a conductive graphene derivative dispersible in water that can be prepared on a large scale from fluorographene. Here, we report a synthesis protocol with high reproducibility for preparing GA. The charging/discharging rate stability and cycling stability of GA were tested in a two-electrode cell with a sulfuric acid electrolyte. The rate stability test revealed that GA could be repeatedly measured at current densities ranging from 1 to 20 A g-1 without any capacitance loss. The cycling stability experiment showed that even after 60,000 cycles, the material kept 95.3% of its specific capacitance at a high current density of 3 A g-1. The findings suggested that covalent graphene derivatives are lightweight electrode materials suitable for developing supercapacitors with extremely high durability.
Keywords: cycling stability; pseudocapacitance; supercapacitor; graphene acid